Practical possibilities of more accurate velocity measurements of ultrasonic waves in liquids by means of the resonator method - BALCERZAK, A.; BAZIOR, Z.; KOZŁOWSKI, Z.; PŁOWIEC, R (Archives of Acoustics, 1993)
A precise investigation of the dependence between the resonance frequencies and the frequency for the real resonator cell was carried out using automatic measurement equipment which works in the range of frequency 0.5-10 MHz. This experimental dependence was compared with the theoretical one for the ideal resonator cell. As a result, regularities were found which are important for more accurate velocity measurements in liquids in the whole frequency range used in the resonator method. It was pointed out how on the basis of these results the method of calculating the propagation velocity in the resonator method can be improved and its accuracy increased.